The NU Concept Of Islam Nusantara In Dealing With Radicalism and Terrorism - Murtaufiq, Sudarto (INSTITUT AGAMA ISLAM TARBIYATUT THOLABAH LAMONGAN, INDONESIA, 2018)
NU has explicitly voiced the importance of Muslims within and outside the country to reconsider and rethink the concept of Islam Nusantara in dealing with radicalism and terrorism. It is such a historical consciousness that could be seen clearly from the roles played by the religious social organization in materializing the teachings of Ahlussunnah wal jamaah (Aswaja). On this stand, NU has been capable of brilliantly articulating religious teachings that are at least based on both textual and contextual aspects. The success of NU in propagating the concept of Islam Nusantara is due to the role of its prominent clerics and Muslim scholars (ulema) for skillfully being able to sow the seeds of Islamic teachings in a peaceful and courteous means in the face of any threats posed by the radical and extremist groups. That is why, NU is committed to doing its best services for the country and even taking part in internationalizing its moderate and tolerant teachings of Islam.